Prop Demonstrations in Biology Lectures Facilitate Student Learning and Performance - Farshad Tamari (American Society for Microbiology, 2015)
Science students can benefit from visual aids. In biology lectures, visual aids are usually limited to tables, figures, and PowerPoint presentations. In this IRB-approved study, we examined the effectiveness of the use of five prop demonstrations, three of which are at the intersection of biology and chemistry, in three community college biology courses. We hypothesized that students’ performance on test questions is enhanced by the use of prop demonstrations. Consistent with our hypothesis, we showed that students learn more effectively and perform better on questions that relate to demonstrations than on questions related to lessons that do not have a demonstration component.